Phenology and environment in the presence of secondary metabolites in Psidium guajava L. - Pérez, Evelyn; Ettiene, Gretty; Ramírez, Maribel; Gómez, Ángel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Guava (Psidium guajava L.) is one of the most important fruit trees in Venezuela due to the acceptance of its fresh and processed fruit with relevant sensory and nutritional characteristics. The establishment of the crop in the producing areas has been the result of the initiative of leading farmers in the country. Due to the potential of guava, the present review aimed to describe the phenology, environment, and presence of secondary metabolites in P. guajava. The search for information on P. guajava included several key words such as phenology, flowering, fruiting, and secondary metabolism. Sixty-six references were selected from 130 results, including research articles, reviews, and books published between 1991 and 2023. Secondary metabolite biosynthesis is a dynamic process that depends on numerous factors associated with the plant and the environment. The content of phenols and flavonoids in guava can help characterize its production, agroindustrial, and pharmaceutical importance, be a tool for cultivar selection, and anticipate the content of other secondary metabolites to identify plants that differ in their production.